(Post-)colonial Myths in German History Textbooks, 1989–2015. Issue 1 (1st March 2021) - Helfer, Florian
Abstract: This article examines the evolution of textbook representations of colonialism in two North Rhine-Westphalian textbook series for the Sekundarstufe II since 1989. On the one hand, the article shows that the developing post-colonial discourse in the German public debate had a particularly strong impact on schoolbooks in the mid-2000s. Textbooks reacted quickly to changes in the public debate and have increasingly attempted to deconstruct colonial narratives. However, implicit mental conceptions of African "backwardness" continue to exert some influence even on today's textbook generation. On the other hand, the article identifies the distortions that appear when colonialism as a global phenomenon is discussed within a curricular framework that focuses on national and European history. Because of the close curricular link between High Imperialism and World War I, textbooks strongly focus on the global rivalry of the European powers, whereas other aspects of colonialism come up short.